Two Different Export-oriented Growth Strategies under a Wage-led Accumulation Regime: a la Turca and a la South Korea - Onaran, Özlem; Stockhammer, Engelbert (Elsevier BV, 2002)
The aim of the paper is to compare the relationship between distribution, growth, accumulation and employment in Turkey and South Korea. These countries represent two different export-oriented growth experiences. The results of the adjustment experiences of both countries are in striking contrast to orthodox theory, however they also present counter-examples to each other in terms of their ways of integrating into the world economy. Thereby they provide examples for comparing different economic policies. The paper tests whether accumulation and employment are wage-led in these two countries by means of a post-Keynesian open economy model, that includes a demand-driven labor market and a reserve army effect in the Marxian sense. The model is estimated in a structural vector autoregression form, in order to capture the complex simultaneous interaction between distribution, accumulation, growth and employment within a systems approach. This model, and the method of estimation are the two innovations of this paper in addressing the crucial policy issues related with structural adjustment problems in developing countries. The results show that decreasing the wage share does not stimulate accumulation, growth and employment. Interestingly, the relation between wage share, investment, growth and employment is similar in both Turkey and South Korea; however the former experienced low and the latter high growth rates due to different export-oriented growth strategies. The explanation of this difference is found in the field of institutions, power structures, and state policies.
Keywords: Accumulation, distribution, export-oriented growth, structural adjustment, post-Keynesian economics